Implementasi Pemikiran KH Hasyim Asyari tentang Etika Murid kepada Guru (Studi atas Pembentukan Karakter Siswa di SMP Maarif Sangatta Utara) - Muhammad Yasin (Al-Rabwah, 2020)
The implementation of Hasyim Asy'ari's thought is quite important, meaning that in the midst of a state of the education system that is trapped in material-oriented. In other words, the teacher views that education is the only place to produce an independent responsible output as an ethical person. So what will happen is the creation of aspects of religious ethics and blessings in education. In the formation of Akhlakul Karimah / Character education at SMP Ma'arif Sangatta Utara applying the Vision and Mission indicators set out in school rules, which must be adhered to by all school members, for example: reading prayers together, students' promises on the page before entering the room. Each class also memorizes short letters before the delivery of lessons as a predetermined schedule. Likewise, when the lesson ended, the students also read the prayers together then left the classroom, shaking hands with the teacher.